STRUKTUR DAN KOMPOSISI PENYUSUN HABITAT YANG DIGUNAKAN OLEH KANGKARENG PERUT-PUTIH (Anthracoceros albirostris) DI ZONA PEMANFAATAN RESORT BAMA TAMAN NASIONAL BALURAN - Nurdiansyah, Rizal; Aji, Irwan Mahakam Lesmono; Syaputra, Maiser (JURNAL RIMBA LESTARI, 2022)
Abstract Oriental pied hornbill (Anthracoceros albirostris) is a protected species based on Law No. 5 of 1990 on Conservation of Natural Resources and Ecosystems and Government Regulation No. 7 of 1999 concerning Preservation Plants and Animals. One area that is identified as habitat of oriental pied hornbill (Anthracoceros albirostris) in Java is in Utilization Zone of Bama Resort Baluran National Park. This study aims to determine the structure and composition of the constituent elements of habitat used by oriental pied hornbill (Anthracoceros albirostris) in Utilization Zone of Bama Resort Baluran National Park. Data collection methods include, literature review, interviews and observation. Data collected coversbiotic and abiotic components and vegetation. The method employed in this research is IPA method (Indeces Ponctuele del'Abondance) for the determination of the existence of Oriental pied hornbill (Anthracoceros albirostris), and employed a single plot method to observe the vegetation. The results show that the total trees used by oriental pied hornbill (Anthracoceros albirostris) is 14 species, consisting of ten species for cover, six species for food, two species for perches, one species for rest, and no trees were found for nesting. Trees with the highest usage frequency is gondang (Ficus variegata) usedas feed tree with adiameter of 92 cm, height of 25 m, and crown cover of 18,80 m2, with daily temperatures ranged from 29,48Â°C to 29,79Â°C, average daily humidity from 84,57% to 85,10% and light intensity from 0,7 lux to 4.460 lux. The species with the highest Importance Value Index is gebang (Corypha utans) witha value of 157,70.